A Call for a Global Constitutional Convention Focused on Future Generations. Issue 3 (4th September 2014) - Gardiner, Stephen M.
<x content-type="archive" xml:space="preserve">Abstract</x> The Carnegie Council's work "is rooted in the premise that the incorporation of ethical concerns into discussions of international affairs will yield more effective policies both in the United States and abroad." In honor of the Council's centenary, we have been asked to (briefly) present our views on the ethical and policy issues posed by climate change, focusing on what people need to know that they probably do not already know, and what should be done. In that spirit, this essay argues that climate change poses a profound ethical challenge, that the ongoing evasion of this challenge produces ineffective policy, and, therefore, that a fundamental paradigm shift is needed. More specifically, I maintain that the climate problem is usually misdiagnosed as a traditional tragedy of the commons, that this obscures two deeper and distinctively ethical challenges (what I call the tyranny of the contemporary and the perfect moral storm), and that we should address these challenges head on, by calling for a global constitutional convention focused on future generations.